Agent-based modeling of inflation dynamics: Interactions between market structure, firm pricing, expectations, and central bank in Türkiye - Demirtas, Sukru C.; Sahin, Senem Cakmak (CENTRAL BANK REPUBLIC TURKEY, 2026)
The persistence of inflation in both advanced and emerging economies calls for a deeper understanding of the underlying mechanisms. This study presents an agent-based model that examines the interaction between market structures, pricing behavior, and expectations in shaping inflationary outcomes. The model encompasses firms, consumers, the central bank, and investors, and examines the interactions of these agents under external shocks, including supply chain disruptions, energy price fluctuations, and trade policy changes. Firms set prices according to their cost structures and profit margins, while consumers dynamically adjust their consumption patterns and inflation expectations. The central bank responds to inflation deviations by adjusting interest rates, while investors reallocate wealth according to market conditions. The parameterization of key economic variables allows for a variety of simulations and provides insights into inflation management. Simulation results illustrate the nonlinear and feedback-driven nature of inflationary dynamics. Moreover, the study contributes to economic policy debates by showing how central bank interest rate interventions affect inflation. The paper not only highlights new perspectives that ABM offers for macroeconomic stability and policy design, with implications for future research directions, but also explores how inflation evolves in the face of various shocks and how the central bank responds to these inflation shocks through inflation targeting.
Keywords: Agent-based modeling; Inflation dynamics; Central bank; Pricing; Heterogeneous agents; Shocks; Business & Economics